Otoritas Keagamaan Guru Ngaji Qudsiyyah - Ubaidillah, Khasan (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The Essence of guru ngaji is a teacher who teaches religion & religiosity. It means that guru ngaji has full authority to teach the religious science and behavior. As a religious teacher, guru ngaji has more religious content. It is positively culminated in the theory (religion) and implementation of religiousness (religiosity). These two key elements will determine the authority of guru ngaji in improving the productivity of santri’s learning process. Even since the Dutch colonial era, guru ngaji, noted well as Kyai, has a very significant authority related to the transformation process of the religious science in shaping santri’s behavior that is sociable to civilization. Therefore, in this article, the author would critically and comprehensively examine a study of the religious authority on the North Coast of Central Java, especially in Madrasah Qudsiyyah Kudus.